Captioned Video: Making It Work for You - Randall S. Davis (Asociación Colombiana de Profesores de Ingles, 2016)
For the past several decades, teachers have been continually trying to exploit and manipulate video to enhance classroom teaching and language learning. When captioned technology emerged to the forefront more than 15 years ago, many educators quickly recognized its potential in helping students process language differently via this additional modality: the printed word (Goldman, 1996; Holobow, Lambert & Sayegh, 1984; Koskinen, Wilson, Gambrell, & Neuman, 1993; Parks, 1994; Vanderplank, 1993).